The scenario of supply chain management in Kuwait food industry - Alrashidi, Abdullah E. M. F.; Al Hazza, Muataz Hazza Faizi; Khan, Ahsan Ali (Deer Hill Publications, 2018)
Supply chain management (SCM) has been well known to influence the company performance in food manufacturing industries. However, the implication of SCM depends on type and culture of the companies. This paper presents the scenario of SCM in Kuwait food industry. In this study quality, time, information, flexibility, and integration have been selected as variables to predict their influence on Kuwait food industries. The methodology of the study was developed where five hypotheses have been proposed on the relationship among the selected factors and the performance. To evaluate the hypotheses, an examination through a questionnaire was conducted, followed by data analysis using Statistical Package (SPSS) and Minitab applications. It was found that out of five proposed hypothesis only two of them were supported by the analytical results. The accepted two hypothesis are related to the quality of supply chain and time management in supply chain to positively effect on the performance of food manufacturing companies. Oher three hypotheses were rejected. Information network, company flexibility and integration among the supply chain components were found to have no significant influence on the performance of food manufacturing industries in Kuwait. This study ranked the factors to prioritize to improve the performance.